Targeting Human Immunodeficiency Virus (HIV) Type 2 Integrase Protein into HIV Type 1 - Liu, Hongmei (American Society for Microbiology, 1999)
Integrase (IN) is the only retroviral enzyme necessary for the integration of retroviral cDNA into the host cell’s chromosomes. The structure and function of IN is highly conserved. The human immunodeficiency virus type 2 (HIV-2) IN has been shown to efficiently support 3′ processing and strand transfer of HIV-1 DNA substrate in vitro. To determine whether HIV-2 IN protein (IN(2)) could substitute for HIV-1 IN function in vivo, we used HIV-1 Vpr to deliver the IN(2) into IN mutant HIV-1 virions by expression in trans as a Vpr-IN fusion protein. Trans-complementation with IN(2) markedly increased the infectivity of IN-minus HIV-1. Compared with the homologous trans-IN protein, infectivity was increased to a level of 16%. Since IN has been found to play a role in reverse transcription (Wu et al., J. Virol. 73:2126–2135, 1999), cells infected with IN(2)-complemented HIV-1 were analyzed for DNA products of reverse transcription. DNA levels of approximately 18% of that of wild type were detected. The homologous trans-IN protein restored the synthesis of viral cDNA to approximately 86% of that of wild-type virus. By complementing integration-defective HIV-1 IN mutant viruses, which were not impaired in cDNA synthesis, the trans-IN(2) protein was shown to support integration up to a level of 55% compared with that of the homologous trans-IN protein. The delivery of heterologous IN protein into HIV-1 particles in trans offers a novel approach to understand IN protein function in vivo.